Rectifying ionic diode based on gel polymer electrolytes - Jiang, Fan (Nanyang Technological University, 2023)
Iontronics rely on ions as charge carriers to produce and transmit signals, mimicking the information processing in biological system. Thus, iontronics exhibit great potential in neuromorphic devices for biological processor and memory. Various structures have been employed to design iontronics and demonstrate rectification, including ion-exchange membranes, nanopores and polyelectrolytes. However, they suffer from liquid leakage and evaporation, sophisticated machining process, low conductivity, and narrow electrochemical window due to water electrolysis. In this research, gel polymer electrolytes (GPE) with high-boiling point solvent are applied to construct the ionic diode. PMMA and PVDF-HFP are chosen as the polymer matrices, and propylene carbonate combined with ionic liquid and salt provide high ionic conductivity and thermal stability. Two gel polymer electrolytes are assembled to form the ionic diode, of which the rectification is based on different diffusion and migration of ions in the GPEs. The I-V characteristics and transient current responses of the GPE heterojunction reveal outstanding rectifying ratio of 23.11, which operates from low temperature at −20 °C (antifreezing) to high temperature at 125 °C (thermal tolerance). The absence of redox (or faradaic) reactions is verified in the cyclic voltammogram and responses of ionic double layer are displayed with ac impedance under different dc biases, further proving the role of ionic diffusion in the current-voltage behavior. To demonstrate further application, the asprepared GPE ionic diode is used to realize the construction of ionic logic gates OR and AND for signal communication. Furthermore, rectification of alternating voltage generated by a triboelectric nanogenerator is demonstrated. The latest development is fully 3Dprinted GPE ionic diodes on soft substrate. Various kinds of carbon powder are prepared into carbon inks and tested for optimal printable carbon electrodes with wide electrochemical window. The fully 3D-printed GPE ionic diode displays good flexibility and durability by maintain 87% of original rectifying ratio under bending state. Finally, SEM and KPFM were employed to further analyze the printed electrodes and GPE heterojunction.